2023
DOI: 10.3389/fmicb.2023.1234884
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate approach to explore the volatolomic and sensory profiles of craft Italian Grape Ale beers produced with novel Saccharomyces cerevisiae strains

Rocchina Pietrafesa,
Gabriella Siesto,
Maria Tufariello
et al.

Abstract: This study investigated the influence of three Saccharomyces cerevisiae strains, selected from different matrices - CHE-3 (cherry), P4 (sourdough) and TA4-10 (grape must) - on characteristics of Italian Grape Ale (IGA) beers obtained at microbrewery scale. A multidisciplinary approach, combining results from analysis of chemical, volatile and organoleptic profiles of the beers, was adopted to underline the relationships between yeast starter and the quality of final products. Detection volatile organic compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…By visually grouping similar samples based on the concentrations of phytochemical components, heatmaps helped identify clusters of samples that share similar compositional characteristics. In support of the utilization of hierarchical clustering heatmaps in exploring complex datasets and PCA, Pietrafesa et al [30] Kaya [31] a emphasized the importance of these methods in their study of multivariate analysis of phytochemical data in plant sciences. Additionally, our PCA and Heatmap results are consistent with previous research reports [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…By visually grouping similar samples based on the concentrations of phytochemical components, heatmaps helped identify clusters of samples that share similar compositional characteristics. In support of the utilization of hierarchical clustering heatmaps in exploring complex datasets and PCA, Pietrafesa et al [30] Kaya [31] a emphasized the importance of these methods in their study of multivariate analysis of phytochemical data in plant sciences. Additionally, our PCA and Heatmap results are consistent with previous research reports [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have reported that S. cerevisiae baker's yeast strains can be employed to ferment brewer's wort [7,[14][15][16][17] and are typically used to brew common Eastern European beers like kvass [18] and Finland's sahti [19,20]. Sourdough cultures are also interesting reservoirs of maltose-negative yeasts for low-alcohol beer brewing [21], fruit beers [22] and craft beers with potential healthy added value [23][24][25][26]. Beers obtained using sourdough strains are also characterized by aromatic differences that are in consonance with their specific metabolic features, which appear to promote the synthesis of volatile compounds [14], in particular esters [1], instead of the fuse alcohols more abundant in brewing yeasts [27].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a large amount of literature concerning the priming composition during the refermentation step [11][12][13], poorly or not investigated at all is the quantity of sugar added for refermentation and its effects on physico-chemical and organoleptic characteristics of beers.…”
Section: Introductionmentioning
confidence: 99%